Identifikasi Materi Praktikum Mahasiswa Pendidikan Biologi FKIP UMS 2015/2016 dalam Implementasi Kurikulum 2013 SMP Bidang IPA Kelas IX - Herlina, Rokhiyani; , Dra. Hariyatmi, M.Si (2016)
Practical Biology is part of the course in Biology in University of Muhammadiyah Surakartais expected to equip the lab materials to the students of Biology Education in University of Muhammadiyah Surakartaand supports the objectives of science teaching curriculum of 2013. This study aims to determine the suitability of the materials lab in Biology Education in University Muhammadiyah of Surakartain academic year 2015/2016 with the IX grade junior high school of science textbooks curriculum2013. the methodsof this researchare the method of documentation and interview method. The type of this research is a qualitative descriptive research by using triangulation techniques, which is seeking and analyzing compatibility between practicummaterial student of Biology EducationinMuhammadiyah University of Surakarta 2015/2016 with the material in the book of Science for Junior 2013 at Class IX, as well as decrypt interviews of lecturers lab course in Biology Laboratory FKIP UMS 2015/2016. The result of this identification are 16 materials (12.6%) of Biological practice at Muhammadiyah University of Surakarta in the category exists and in accordance with the Laboratory Material of Science in junior Class IX Curriculum 201; 79 materials (62.2%) fall into the category exists for the enrichment of alumnus; and 32 materials (25.2%) are categorized yet, it is because the Laboratory materials such as physics and chemistry lab are not practiced yet inMuhammadiyah University of Surakarta and in Muhammadiyah University of SurakaraPracticum prefers to practice in biology and its enrichment.